A Review on the Valorization of Macroalgal Wastes for Biomethane Production - Yann Nicolas Barbot; Hashem Al-Ghaili; Roland Benz (Marine Drugs, 2016)
The increased use of terrestrial crops for biofuel production and the associated environmental, social and ethical issues have led to a search for alternative biomass materials. Terrestrial crops offer excellent biogas recovery, but compete directly with food production, requiring farmland, fresh water and fertilizers. Using marine macroalgae for the production of biogas circumvents these problems. Their potential lies in their chemical composition, their global abundance and knowledge of their growth requirements and occurrence patterns. Such a biomass industry should focus on the use of residual and waste biomass to avoid competition with the biomass requirements of the seaweed food industry, which has occurred in the case of terrestrial biomass. Overabundant seaweeds represent unutilized biomass in shallow water, beach and coastal areas. These eutrophication processes damage marine ecosystems and impair local tourism; this biomass could serve as biogas feedstock material. Residues from biomass processing in the seaweed industry are also of interest. This is a rapidly growing industry with algae now used in the comestible, pharmaceutical and cosmetic sectors. The simultaneous production of combustible biomethane and disposal of undesirable biomass in a synergistic waste management system is a concept with environmental and resource-conserving advantages.